Incentive-based extinction of safety behaviors: Positive outcomes competing with aversive outcomes trigger fear-opposite action to prevent protection from fear extinction. (October 2019) - Pittig, Andre
Abstract: Maladaptive safety behavior maintains fear and anxiety by prohibiting inhibitory learning about the non-occurrence of feared outcomes (known as protection from extinction). Not engaging in safety behavior, however, requires to act opposite to fear-motivated behavioral tendencies. The initiation of such fear-opposite action by positive outcomes, which were in conflict with safety behavior, was tested. Following fear acquisition to a warning signal (CS+), participants acquired safety behavior to prevent the aversive outcome (n = 48). Next, safety behavior also prevented gaining rewards. In a control group (n = 50), neutral outcomes were presented to control for novelty effects of the second outcome. Subsequently, no aversive outcome occurred anymore. Phases with safety behavior were intermitted by phases without safety behavior being available to examine cognitive and physiological indicators of fear and anxiety. Without competing positive outcomes, safety behavior was frequently executed, persisted in absence of the aversive outcome, and prohibited extinction learning. Positive outcomes clearly reduced safety behavior despite equal levels of acquired fear. This enabled fear extinction as soon as the aversive outcome was absent. Importantly, this extinction learning resulted in attenuated fear and anxiety responses when safety behavior became unavailable. Post-hoc findings indicated that the mere anticipation of positive outcomes slightly reduced safety behavior. Thus, competing positive outcomes triggered fear-opposite action that prevented persistent safety behavior and protection from extinction. Highlights: Tested incentive-based extinction of safety behavior (SB) and impact on fear and anxiety. SB frequent, persistent, linked to protection from extinction w/o competing positive outcomes. Positive outcomes reduced SB despite same levels of acquired fear and anxiety. Reduced SB enabled fear extinction as soon as the aversive event was absent. Incentive-based extinction prevented persistent SB and protection from extinction.